A bioinspired self-pumping Janus interface for wet-adhesive epidermal ECG monitoring - Zhiwei Jiang; Yaping You; Hui Zhang; Cihui Liu; Shaohong Wu; Zixiang Li; Songchao Fu; Xia Liu; Yiran Jing; Yuzhen Li; Cheng Chen; Lehao Ren (Chemical Engineering Journal, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Sub-chronic copper exposure alters growth performance, intestinal histopathology, and intestinal microbiota in adult zebrafish (Danio rerio) - Yaping Wang; Yaqian Fu; Xuyang Zhai; Chang Dong; Mengdie Yang; Ziyi Huang; Fei Liu (Ecotoxicology, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Systematic review on atmospheric pollution during highway construction through multiple monitoring data-source - Shanqian Huang; Xinjun Wang; Chunying Lu; Jinsheng Fu; Yaping Kong (Transportation Research Part D: Transport and Environment, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

An Advanced Fluorescent Molecularly Imprinted Sensor Based on Carbon Quantum Dots for Highly Sensitive Detection of 6-Mercaptopurine - Yinuo Liu; Zhengyuan Dai; Ying Wang; Shanshan Fu; Li Li; Yaping Ding (Journal of Fluorescence, 2025)

Environmental variables affect the effectiveness of ecosystem services of ecological restoration project: Evidence from Xiangjiang River Basin-Dongting Lake - Shu Fu; Jianjun Zhang; Yufei Li; Wei Chen; Yaping Zhang; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Effect of labor migration on famers’ biopesticide application --mediating effect based on social network - Ruixin Zhang; Yexing Yin; Yushi Chen; Jinyang Sun; Yuying Liu; Xinhong Fu; Yaping Wang (Environment, Development and Sustainability, 2025)

Integrated harvest and distribution scheduling of fresh agricultural products for multiple farms using a Q-learning-based artificial bee colony algorithm with problem knowledge - Xiaomeng Ma; Xujin Pu; Yaping Fu; Yuan Wang (Swarm and Evolutionary Computation, 2025)

Response of ecological condition in ecologically fragile areas to disturbance from extreme precipitation event: An empirical analysis from the loess plateau - Kexin Yi; Jianjun Zhang; Haoyi Lei; Wei Chen; Yaping Zhang; Shu Fu; Ke Wang (Journal of Cleaner Production, 2025)

Impact of vacuum treatment on multi-layered structure and physicochemical properties of reconstituted fish steaks: Specific effects of air distribution within meat-air systems - Yaping Fu; Yanshun Xu (Journal of Food Engineering, 2025)

Improving resilience to extreme heat events through green space morphology: A threshold-based perspective - Yixin Dai; Jianjun Zhang; Shu Fu; Wei Chen; Yaping Zhang; Kexin Yi (Sustainable Cities and Society, 2025)

Open shop scheduling with group and transportation operations by learning-driven hyper-heuristic algorithms - Yifeng Wang; Yaping Fu; Kaizhou Gao; Humyun Fuad Rahman; Min Huang (Swarm and Evolutionary Computation, 2024)

A Q-learning based artificial bee colony algorithm for solving surgery scheduling problems with setup time - Ruixue Zhang; Hui Yu; Kaizhou Gao; Yaping Fu; Joong Hoon Kim (Swarm and Evolutionary Computation, 2024)

Heating pattern and effects of built-up land in response to influencing factors: A statistical estimation of 172 Chinese cities - Wei Chen; Jianjun Zhang; Yaping Zhang; Shu Fu; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2024)

Therapeutic Effect of Smilax glabra Roxb. on Weaning Rats Against Pb-Induced Nephrotoxicity Based on Network Pharmacology - Chongmei Tian; Meiting Yu; Yuejuan Fang; Yaping Zhao; Liping Fu; Jingbai Chen; Daozong Xia (Biological Trace Element Research, 2024)

Multi-layered structure and physicochemical properties of reconstituted meat-based products from minced fish by physical extrusion: Impact of extrusion strength - Yaping Fu; Yanshun Xu (Food Research International, 2024)

Selenium protects against Pb-induced renal oxidative injury in weaning rats and human renal tubular epithelial cells through activating NRF2 - Chongmei Tian; Yu Qiu; Yaping Zhao; Liping Fu; Daozong Xia; Junjie Ying (Journal of Trace Elements in Medicine and Biology, 2024)

Optical sensors of volatile organic compounds for non-invasive diagnosis of diseases - Xiaoyun Qu; Yaping Hu; Chenggang Xu; Yue Li; Lin Zhang; Qiao Huang; Sareh Sadat Moshirian-Farahi; Jianmin Zhang; Xiahong Xu; Ming Liao; Yingchun Fu (Chemical Engineering Journal, 2024)

Multi-objective migrating birds optimization for solving stochastic home health care routing and scheduling problems considering caregiver working time constraints - Yaping Fu; Xiaomeng Ma; Kaizhou Gao; Hongfeng Wang; Ali Sadollah; L.Y. Chen (Swarm and Evolutionary Computation, 2024)

A cooperative evolutionary algorithm with simulated annealing for integrated scheduling of distributed flexible job shops and distribution - Zhengpei Zhang; Yaping Fu; Kaizhou Gao; Hui Zhang; Lei Wang (Swarm and Evolutionary Computation, 2024)

Integrated scheduling problems of open shop and vehicle routing using an ensemble of group teaching optimization and simulated annealing - Jiaming Su; Yaping Fu; Kaizhou Gao; Hongyu Dong; Jianhui Mou (Swarm and Evolutionary Computation, 2023)

Purification and characterization of a glycoprotein from Sipunculus nudus and its immune-enhancing activity to RAW 264.7 macrophages - Xuli Lu; Yaping Dai; Shengtao Yang; Tengfei Fu; Yunxia He; Fanke Zeng; Tinghui Chen; Yupo Cao; Ruyi Li; Jihua Li; Wei Zhou (Food Research International, 2023)

Superior solar water purification achieved by the excellent photothermal conversion and thermal management of porous plasmonic TiN nanoparticles - Yaping Gao; Xiaojie Zhou; Nuo Fu; Sihua Su; Baopeng Ma; Qifeng Ruan; Di Wu; Nan Zhang; Ziwei Deng; Ruibin Jiang (Chemical Engineering Journal, 2023)

Enhancing efficiency of biological contact oxidation reactors through filaments optimization of basalt fibers bio-carriers: Insights from a pilot-scale study - Huicheng Ni; Muhammad Arslan; Tiancai Zhang; Lizhuang Chen; Yaping Wang; Junchao Qian; Fu Cao; Zhiren Wu; Mohamed Gamal El-Din (Journal of Water Process Engineering, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Facilitating photogenerated carrier transfer and water oxidation kinetics of BiVO4 photoanode via novel Zn@Co3C functional layer - Weibing Li; Liming Wang; Jie Zhou; Ning Wang; Xinyang Fu; Yibo Wang; Yuyu Bu; Yaping Zhang; Lei Wang (Chemical Engineering Journal, 2023)

Dual-emitting cellulose nanocrystal hybrid materials with circularly polarized luminescence for anti-counterfeiting labels - Lingxiao Xing; Guihua Li; Yaping Sun; Xu Wang; Zaiwu Yuan; Yingjuan Fu; Menghua Qin (Carbohydrate Polymers, 2023)

A novel Q-learning based variable neighborhood iterative search algorithm for solving disassembly line scheduling problems - Yaxian Ren; Kaizhou Gao; Yaping Fu; Hongyan Sang; Dachao Li; Zile Luo (Swarm and Evolutionary Computation, 2023)

AraENCODE: A comprehensive epigenomic database of Arabidopsis thaliana - Zhenji Wang; Minghao Liu; Fuming Lai; Qiangqiang Fu; Liang Xie; Yaping Fang; Qiangwei Zhou; Guoliang Li (Molecular Plant, 2023)

Coordination number engineering of Zn single-atom sites for enhanced transfer hydrogenation performance - Yaping Song; Rou Guo; Binbin Feng; Yanghe Fu; Fumin Zhang; Yifei Zhang; De-Li Chen; Jiangwei Zhang; Weidong Zhu (Chemical Engineering Journal, 2023)

Design, synthesis and biological evaluation of aminopyrimidine derivatives bearing dihydroquinoxalinone as novel EGFRL858R/T790M kinase inhibitors against non-small-cell lung cancer - Liping Fu; Yu Cao; Jingbai Chen; Ruoyu He; Yanmei Zhao; Yaping Zhao; Jianjun Xi; Rangxiao Zhuang; Chongmei Tian (Medicinal Chemistry Research, 2023)

The spatial configuration of buildings: A vital consideration impossible to ignore in regulating urban land surface temperature? Evidence from 35 Chinese cities - Wei Chen; Jianjun Zhang; Shidong Liu; Sen Liang; Yaping Zhang; Shu Fu (Science of The Total Environment, 2023)

Dual-objective modeling and optimization of a low-carbon waste-classified collection problem - Xulong Lu; Xujin Pu; Hongfeng Wang; Yaping Fu (Environmental Science and Pollution Research, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

A Significant Fluorescent Aptamer Sensor Based on Carbon Dots and Graphene Oxide for Highly Selective Detection of Progesterone - Hanyue Cui; Huan Lu; Jing Yang; Yao Fu; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

A multi-stage supply chain disruption mitigation strategy considering product life cycle during COVID-19 - Jingze Chen; Hongfeng Wang; Yaping Fu (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Modeling and optimization for noise-aversion and energy-awareness disassembly sequence planning problems in reverse supply chain - Pei Liang; Yaping Fu; Songyuan Ni; Bing Zheng (Environmental Science and Pollution Research, 2021)

Sediment transport under increasing anthropogenic stress: Regime shifts within the Yellow River, China - Shuang Song; Shuai Wang; Bojie Fu; Yanxu Liu; Kevin Wang; Yikai Li; Yaping Wang (Ambio, 2020)

MiR-221-3p regulates the microvascular dysfunction in diabetic retinopathy by targeting TIMP3 - Chongxian Wang; Yuling Lin; Yanqin Fu; Dongming Zhang; Yaping Xin (Pflügers Archiv - European Journal of Physiology, 2020)

Monoclonal Antibody-Based Treatments for Neuromyelitis Optica Spectrum Disorders: From Bench to Bedside - Wenli Zhu; Yaling Zhang; Zhen Wang; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2020)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Erratum to: Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2019)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2017)

Novel rice mutants overexpressing the brassinosteroid catabolic gene CYP734A4 - Wenjing Qian; Chao Wu; Yaping Fu; Guocheng Hu; Zhengquan He; Wenzhen Liu (Plant Molecular Biology, 2017)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

Modulation of hsa-miR-26b levels following adipokine stimulation - Guangfeng Xu; Chenbo Ji; Chunmei Shi; Hailong Fu; Lingling Zhu; Lu Zhu; Lulian Xu; Ling Chen; Yueying Feng; Yaping Zhao; Xirong Guo (Molecular Biology Reports, 2013)

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

Isolation and characterization of a rice mutant with narrow and rolled leaves - Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Shihua Cheng; Wenzhen Liu (Planta, 2010)

Identification and characterization of HTD2: a novel gene negatively regulating tiller bud outgrowth in rice - Wenzhen Liu; Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Weijiang Luan; Zhengquan He; Zongxiu Sun (Planta, 2009)

Identification and fine mapping of a thermo-sensitive chlorophyll deficient mutant in rice (Oryza sativa L.) - Wenzhen Liu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Chao Wu; Zongxiu Sun (Planta, 2007)